2015
DOI: 10.1016/j.celrep.2015.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Defective TFH Cell Function and Increased TFR Cells Contribute to Defective Antibody Production in Aging

Abstract: Summary Defective antibody production in aging is broadly attributed to immunosenescence. However, the precise immunological mechanisms remain unclear. Here we demonstrate an increase in the ratio of inhibitory T follicular regulatory (Tfr) cells to stimulatory T follicular helper (Tfh) cells in aged mice. Aged Tfh and Tfr cells are phenotypically distinct from those in young mice, exhibiting increased PD-1 expression but decreased ICOS expression. Aged Tfh cells exhibit defective antigen-specific responses, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
107
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(122 citation statements)
references
References 29 publications
(47 reference statements)
14
107
1
Order By: Relevance
“…This is seen most clearly when we compare the Th1 to Tfh ratios as demonstrated in Figure 5E, where most of the ratios from aged cohorts are less than 2 and those from young cohorts range to over 50. Our results confirm those of Sage and colleagues [49] who also reported similar enhancement of the Tfh population in aged mice. This difference in Th subset distribution between young and aged groups could account for the fact that aging has a greater impact on the generation of lung-homing Th1 effectors rather than on Tfh cells and antibody production.…”
Section: Discussionsupporting
confidence: 93%
“…This is seen most clearly when we compare the Th1 to Tfh ratios as demonstrated in Figure 5E, where most of the ratios from aged cohorts are less than 2 and those from young cohorts range to over 50. Our results confirm those of Sage and colleagues [49] who also reported similar enhancement of the Tfh population in aged mice. This difference in Th subset distribution between young and aged groups could account for the fact that aging has a greater impact on the generation of lung-homing Th1 effectors rather than on Tfh cells and antibody production.…”
Section: Discussionsupporting
confidence: 93%
“…3a and Supplementary Fig. 2a), as previous studies performed181920. Both CD4 + CXCR5 hi PD-1 hi and CD4 + CXCR5 hi ICOS hi Tfh cells expressed the highest levels of Tfh-associated molecules CXCR5, PD-1 and ICOS, as well as the memory/activation marker CD44, compared with the other three subsets (Fig.…”
Section: Resultssupporting
confidence: 82%
“…However, regulatory CD4 + T cells are also found within GCs,235 and recent studies have shown that a subset of CXCR5 +  FoxP3 +  CD4 + Treg cells, termed T follicular regulatory (Tfr) cells, are generated as immune responses are induced and localize to the GC to control the GC response 236, 237, 238. In mice, Tfr cells have been shown to reduce antibody production and the number of GC B cells, antigen‐specific B cells, and plasma cells 236, 237, 238, 239, 240, 241. Multiple stages of the B‐cell differentiation process are inhibited, from initial B‐cell activation to the generation of class‐switched B cells and plasma cells.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%